Stent composite material as well as preparation method and application thereof

Through the composite material of graphene oxide and polylactic acid, spinal scaffolds are prepared using 3D printing technology, which solves the problem of insufficient biocompatibility and bone integration capabilities of traditional materials, and realizes the mechanical, conductive and antibacterial optimization of the material, which is suitable for spinal columns. Implantation has promoted the advancement of spinal implant technology.

CN119158086APending Publication Date: 2024-12-20KUNMING UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411310949.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional spinal stent materials have shortcomings in terms of biocompatibility and bone integration capabilities, and graphene is difficult to effectively apply due to processing difficulty and potential toxic effects.

Method used

The composite material of graphene oxide and polylactic acid is used to prepare the scaffolding composite material through a 3D printing process, and combined with annealing treatment, a graphene oxide/polylactic acid composite wire with excellent mechanical, conductive and antibacterial properties is formed, which is used to prepare spinal stents.

Benefits of technology

This material has no obvious toxicity to osteoblasts, promotes cell proliferation and differentiation, induces new bone formation, and has faster and more firm bone integration, with good mechanical properties, electrical conductivity and antibacterial properties. It is suitable as a medical implant material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of medical implant materials, in particular to a stent composite material and a preparation method and application thereof. The invention provides a stent composite material preparation method, which comprises: mixing a graphene oxide dispersion liquid and a polylactic acid dispersion liquid, and sequentially carrying out curing and melt extrusion to obtain a 3D printing graphene oxide / polylactic acid composite wire, sequentially carrying out 3D printing on the 3D printing graphene oxide / polylactic acid composite wire rod to obtain a stent; and carrying out annealing treatment on the stent to obtain the stent composite material. The scaffold composite material prepared by the preparation method disclosed by the invention has no obvious toxicity to osteoblasts, but can promote cell proliferation and differentiation; and the scaffold composite material has strong capability of inducing formation of new bones, and osseointegration is faster and firmer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical implant materials, and in particular to a bracket composite material and a preparation method and application thereof. Background Art

[0002] Spinal stents are commonly used implants in spinal surgery. Traditional stent materials are mainly titanium alloys, PEEK, etc. However, although these materials have good mechanical properties, their biocompatibility and bone integration capabilities need to be improved. In recent years, graphene has received widespread attention in the biomedical field due to its excellent mechanical, conductive and antibacterial properties. However, graphene itself is difficult to process and may cause certain toxic effects. Summary of the invention

[0003] The purpose of the present invention is to provide a scaffold composite material and its preparation method and application. The scaffold composite material prepared by the preparation method of the present invention not only has no obvious toxicity to osteoblasts, but can promote cell proliferation and differentiation; and the scaffold composite material has a strong ability to induce new bone formation, and bone integration is faster and firmer.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a scaffold composite material, comprising the following steps:

[0006] After mixing the graphene oxide dispersion and the polylactic acid dispersion, solidification and melt extrusion are performed in sequence to obtain a 3D printed graphene oxide / polylactic acid composite wire;

[0007] 3D printing the 3D printed graphene oxide / polylactic acid composite wire in sequence to obtain a stent;

[0008] The support is subjected to annealing treatment to obtain the support composite material.

[0009] Preferably, the solvent in the graphene oxide dispersion and the solvent in the polylactic acid dispersion independently include one or more of difluoromethane, fluorinated benzene, dimethylacetamide and dimethylformamide.

[0010] Preferably, the mixing is carried out under stirring conditions, the stirring temperature is 28 to 35° C., and the time is 40 to 80 min;

[0011] The polylactic acid dispersion is obtained by mixing polylactic acid and an organic solvent; the mixing temperature of the polylactic acid and the organic solvent is 28-35° C. and the mixing time is 90-180 min.

[0012] Preferably, the curing method is vacuum drying;

[0013] The vacuum drying is carried out at a temperature of 50-70° C. and for 24 hours.

[0014] Preferably, the die temperature of the melt extrusion is 190-210° C., and the screw speed is 12-17 r / min.

[0015] Preferably, the mass ratio of graphene oxide to polylactic acid in the 3D printed graphene oxide / polylactic acid composite wire is (0.001-0.0025):1.

[0016] Preferably, the annealing treatment is carried out in an oven;

[0017] The temperature of the oven is 100-140° C., and the time is 30-90 minutes.

[0018] The present invention also provides a support composite material prepared by the preparation method described in the above technical solution.

[0019] The present invention also provides the use of the scaffold composite material described in the above technical solution in the preparation of medical implant materials.

[0020] Preferably, the medical implant material is a spinal stent material.

[0021] The present invention provides a method for preparing a scaffold composite material, comprising the following steps: mixing a graphene oxide dispersion and a polylactic acid dispersion, and then sequentially curing and melt extruding to obtain a 3D printed graphene oxide / polylactic acid composite wire; sequentially 3D printing the 3D printed graphene oxide / polylactic acid composite wire to obtain a scaffold; and annealing the scaffold to obtain the scaffold composite material. Graphene oxide, as a nanomaterial, has a large specific surface area and excellent electron transport properties, which help promote the adhesion and growth of bone cells, and can also enhance the activity of bone cells and the bone formation process by regulating cell signal transduction pathways. Polylactic acid can be used as a matrix to wrap and isolate graphene nanosheets to a certain extent, and the composite formed by polylactic acid and graphene oxide will also form a barrier at the interface, reducing direct contact and influence on cells, thereby reducing cytotoxicity. In vitro cell experiments show that the scaffold composite material of the present invention not only has no obvious toxicity to osteoblasts, but can promote cell proliferation and differentiation. Animal implantation experiments show that the scaffold composite material of the present invention has a strong ability to induce new bone formation, and bone integration is faster and firmer. The elastic modulus of the scaffold composite material of the present invention is 3-5 GPa, close to cortical bone; the conductivity is 10-100 S / m, which is conducive to the conduction of neural electrical signals; and the antibacterial rate against common pathogenic bacteria such as Staphylococcus aureus and Escherichia coli is greater than 99%.

[0022] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0023] 1) Graphene oxide significantly improves the mechanical strength of the PLA matrix, making it closer to natural bone tissue;

[0024] 2) Graphene oxide gives the composite material good conductivity, which is beneficial to the electrophysiological coupling between the scaffold and the host bone;

[0025] 3) Graphene oxide has a unique antibacterial mechanism that can prevent stent-related infection;

[0026] 4) 3D printing technology enables precise and controllable preparation with a high degree of personalization. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a scaffold composite material, comprising the following steps:

[0028] After mixing the graphene oxide dispersion and the polylactic acid dispersion, solidification and melt extrusion are performed in sequence to obtain a 3D printed graphene oxide / polylactic acid composite wire;

[0029] 3D printing the 3D printed graphene oxide / polylactic acid composite wire in sequence to obtain a stent;

[0030] The support is subjected to annealing treatment to obtain the support composite material.

[0031] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0032] The present invention mixes a graphene oxide dispersion and a polylactic acid dispersion, and then sequentially performs solidification and melt extrusion to obtain a 3D printing graphene oxide / polylactic acid composite wire.

[0033] In the present invention, the mass concentration of graphene oxide in the graphene oxide dispersion is preferably 0.1-1.2wt%, more preferably 0.4-1.1wt%, and most preferably 0.7-1.0wt%. In an embodiment of the present invention, the mass concentration of graphene oxide in the graphene oxide dispersion may be 0.131wt%, 0.113wt% or 0.165wt%. In the present invention, the method for preparing the graphene oxide dispersion preferably comprises: mixing graphene oxide and an organic solvent to obtain the graphene oxide. In the present invention, the graphene oxide is preferably prepared by an improved Hummers method, and the present invention has no special restrictions on the preparation process of the improved Hummers method, and the preparation process well known to those skilled in the art can be used. In the present invention, the organic solvent preferably includes one or more of difluoromethane, fluorinated benzene, dimethylacetamide and dimethylformamide, and more preferably includes dimethylformamide; when the organic solvent is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and can be mixed in any ratio. In the present invention, the mixing is preferably carried out under ultrasonic conditions, the frequency of the ultrasound is preferably 40 kHz; the time is preferably 30 to 180 min, more preferably 60 to 150 min, and most preferably 110 to 130 min. In an embodiment of the present invention, the frequency of the ultrasound can be 40 kHz; the time can be 120 min.

[0034] In the present invention, the mass concentration of the polylactic acid dispersion is preferably 1-6wt%, more preferably 2-5wt%, and most preferably 3-4wt%. In an embodiment of the present invention, the mass concentration of the polylactic acid dispersion can be 3.915wt%. In the present invention, the preparation method of the polylactic acid dispersion preferably includes: mixing polylactic acid and an organic solvent to obtain the polylactic acid dispersion. In the present invention, the organic solvent preferably includes one or more of difluoromethane, fluorinated benzene, dimethylacetamide and dimethylformamide, and more preferably includes dimethylformamide; when the organic solvent is two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and can be mixed in any ratio. In the present invention, the mixing is preferably carried out under stirring, and the stirring temperature is preferably 28-35°C, more preferably 29-34°C, and most preferably 30-33°C; the time is preferably 90-180min, more preferably 100-150min, and most preferably 110-125min. In an embodiment of the present invention, the stirring temperature may be 30° C. and the stirring time may be 120 min.

[0035] In the present invention, the mixing of the graphene oxide dispersion and the polylactic acid dispersion is preferably performed by slowly adding the graphene oxide dispersion to the polylactic acid dispersion while stirring, and continuing to stir after the graphene oxide dispersion is completely added. In the present invention, the addition rate of the graphene oxide dispersion is preferably 1 to 8 mL / min, more preferably 2 to 6 mL / min, and most preferably 3 to 4 mL / min. In an embodiment of the present invention, the addition rate of the graphene oxide dispersion may be 4 mL / min. In the present invention, the stirring temperature is preferably 28 to 35°C, more preferably 30 to 32°C; the continued stirring time is preferably 40 to 80 min, more preferably 50 to 60 min. In an embodiment of the present invention, the stirring temperature may be 30°C and the time may be 60 min.

[0036] In the present invention, the curing method is preferably vacuum drying; the temperature of the vacuum drying is preferably 50-70°C, more preferably 55-65°C, most preferably 58-62°C; the time is preferably 24 hours. In the present invention, the curing is preferably carried out in a stainless steel mold. In an embodiment of the present invention, the temperature of the vacuum drying can be 60°C and the time can be 24 hours.

[0037] In the present invention, the die temperature of the melt extrusion is preferably 190-210°C, more preferably 195-205°C, and most preferably 198-200°C; the screw speed is preferably 12-17r / min, more preferably 13-16r / min, and most preferably 14-15r / min. In an embodiment of the present invention, the die temperature of the melt extrusion can be 200°C and the screw speed can be 16r / min.

[0038] In the present invention, the mass ratio of graphene oxide to polylactic acid in the 3D printed graphene oxide / polylactic acid composite wire is preferably (0.001-0.0025): 1, more preferably (0.0012-0.002): 1, and most preferably (0.0014-0.0016): 1. In an embodiment of the present invention, the mass ratio of graphene oxide to polylactic acid in the 3D printed graphene oxide / polylactic acid composite wire may be 0.002: 1, 0.0015: 1 or 0.0025: 1.

[0039] After obtaining the 3D printed graphene oxide / polylactic acid composite wire, the present invention sequentially 3D prints the 3D printed graphene oxide / polylactic acid composite wire to obtain a stent.

[0040] The present invention does not have any special limitation on the 3D printing process, and printing can be performed according to the target support design parameters using a process well known to those skilled in the art.

[0041] After obtaining the stent, the present invention performs annealing treatment on the stent to obtain the stent composite material.

[0042] In the present invention, the annealing treatment is preferably carried out in an oven; the temperature of the annealing treatment is preferably 100-140°C, more preferably 110-130°C, and most preferably 118-122°C; the time is preferably 30-90 min, more preferably 40-80 min, and most preferably 50-70 min. In an embodiment of the present invention, the temperature of the annealing treatment can be 120°C and the time can be 2 hours. In the present invention, the role of the annealing treatment is to release residual stress and improve the stability and mechanical properties of the stent material.

[0043] The present invention also provides a support composite material prepared by the preparation method described in the above technical solution.

[0044] The present invention also provides the use of the scaffold composite material described in the above technical solution in the preparation of medical implant materials. In the present invention, the medical implant material is preferably a spinal scaffold material. The present invention does not have any special restrictions on the method of the application, and the method well known to those skilled in the art can be used.

[0045] The following is a detailed description of the stent composite material provided by the present invention, its preparation method and application in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0046] Example 1

[0047] 10 mg of graphene oxide and 8 mL of dimethylformamide were mixed under ultrasonic conditions (frequency of 40 kHz, time of 120 min) to obtain a graphene oxide dispersion (mass concentration of 0.131 wt%);

[0048] 5 g of polylactic acid was added to 130 mL of dimethylformamide and mixed under stirring conditions (temperature of 30° C., time of 120 min) to obtain a polylactic acid dispersion (mass concentration of 3.915 wt %);

[0049] The graphene oxide dispersion was slowly added to the polylactic acid dispersion at a rate of 4 mL / min and stirred (temperature was 30°C, time was 60 min), cured by vacuum drying (temperature was 60°C, time was 24 h), and then melt extruded (die temperature was 200°C, screw speed was 16 r / min) to obtain a 3D printed graphene oxide / polylactic acid composite wire;

[0050] According to the spinal stent design parameters, the 3D printed graphene oxide / polylactic acid composite wire is placed in a 3D printer for 3D printing, and then dried at 120° C. for 2 hours to obtain a spinal stent composite material;

[0051] The spinal support composite material was subjected to mechanical property testing, and the testing process was as follows: according to the requirements of ASTM D638, the tensile properties of the sample were tested using a tensile testing machine. The test conditions were room temperature (25°C) and a loading rate of 5mm / min; the test results were: the tensile strength was 3.2MPa;

[0052] The spinal support composite material was tested for electrical conductivity. The test process was as follows: according to ASTM D257, the resistivity of the sample was measured using a resistance meter. The test conditions were room temperature (25°C); the test results were: the electrical conductivity was 50S / m;

[0053] The spinal support composite material was tested for antibacterial performance, and the test process or reference test standard was: according to ASTM E2180, the antibacterial performance of the sample was evaluated. The test bacteria included Escherichia coli and Staphylococcus aureus; the test result was: the antibacterial rate was 99.3%;

[0054] The testing process of the cytotoxicity test is: in accordance with the requirements of ISO 10993-5, cell culture and cell lines are used to evaluate the cytotoxicity of the material by direct contact method; the test result is: the cell survival rate is 75%.

[0055] Example 2

[0056] 7.5 mg of graphene oxide and 7 mL of dimethylformamide were mixed under ultrasonic conditions (frequency of 40 kHz, time of 120 min) to obtain a graphene oxide dispersion (mass concentration of 0.113 wt%);

[0057] 5 g of polylactic acid was added to 130 mL of dimethylformamide and mixed under stirring conditions (temperature of 30° C., time of 120 min) to obtain a polylactic acid dispersion (mass concentration of 3.915 wt %);

[0058] The graphene oxide dispersion was slowly added to the polylactic acid dispersion at a rate of 4 mL / min and stirred (temperature was 30°C, time was 60 min), cured by vacuum drying (temperature was 60°C, time was 24 h), and then melt extruded (die temperature was 200°C, screw speed was 16 r / min) to obtain a 3D printed graphene oxide / polylactic acid composite wire;

[0059] According to the spinal stent design parameters, the 3D printed graphene oxide / polylactic acid composite wire is placed in a 3D printer for 3D printing, and then dried at 120° C. for 2 hours to obtain a spinal stent composite material;

[0060] The spinal support composite material was subjected to mechanical property testing, and the testing process was as follows: according to the requirements of ASTM D638, the tensile properties of the sample were tested using a tensile testing machine. The test conditions were room temperature (25°C) and a loading rate of 5mm / min; the test results were: the tensile strength was 4.0MPa;

[0061] The spinal support composite material is tested for electrical conductivity. The test process is as follows: according to ASTM D257, a resistance meter is used to measure the resistivity of the sample. The test condition is room temperature (e.g., 25° C.); the test result is: the electrical conductivity is 22S / m;

[0062] The spinal support composite material was tested for antibacterial performance, and the test process or reference test standard was: according to ASTM E2180, the antibacterial performance of the sample was evaluated. The test bacteria included Escherichia coli and Staphylococcus aureus; the test result was: the antibacterial rate was 99.4%;

[0063] The testing process of the cytotoxicity test is as follows: in accordance with the requirements of ISO 10993-5, cell culture and cell lines are used to evaluate the cytotoxicity of the material by direct contact method; the test results are: the cell survival rate is 78%.

[0064] Example 3

[0065] 12.5 mg of graphene oxide and 8 mL of dimethylformamide were mixed under ultrasonic conditions (frequency of 40 kHz, time of 120 min) to obtain a graphene oxide dispersion (mass concentration of 0.165 wt%);

[0066] 5 g of polylactic acid was added to 130 mL of dimethylformamide and mixed under stirring conditions (temperature of 30° C., time of 120 min) to obtain a polylactic acid dispersion (mass concentration of 3.915 wt %);

[0067] The graphene oxide dispersion was slowly added to the polylactic acid dispersion at a rate of 4 mL / min and stirred (temperature was 30°C, time was 60 min), cured by vacuum drying (temperature was 60°C, time was 24 h), and then melt extruded (die temperature was 200°C, screw speed was 16 r / min) to obtain a 3D printed graphene oxide / polylactic acid composite wire;

[0068] According to the spinal stent design parameters, the 3D printed graphene oxide / polylactic acid composite wire is placed in a 3D printer for 3D printing, and then dried at 120° C. for 2 hours to obtain a spinal stent composite material;

[0069] The spinal support composite material was subjected to mechanical property testing, and the testing process was as follows: according to the requirements of ASTM D638, the tensile properties of the sample were tested using a tensile testing machine. The test conditions were room temperature (25°C) and a loading rate of 5mm / min; the test results were: the tensile strength was 3.2MPa;

[0070] The spinal support composite material is tested for electrical conductivity. The test process is as follows: according to ASTM D257, a resistance meter is used to measure the resistivity of the sample. The test condition is room temperature (e.g., 25° C.); the test result is: the electrical conductivity is 65 S / m;

[0071] The spinal support composite material was tested for antibacterial performance, and the test process or reference test standard was: according to ASTM E2180, the antibacterial performance of the sample was evaluated. The test bacteria included Escherichia coli and Staphylococcus aureus; the test result was: the antibacterial rate was 99.1%;

[0072] The testing process of the cytotoxicity test is: in accordance with the requirements of ISO 10993-5, cell culture and cell lines are used to evaluate the cytotoxicity of the material by direct contact method; the test results are: the cell survival rate is 76%.

[0073] In summary, the scaffold composite material of the present invention has achieved optimization in mechanics, conductivity, antibacterial and osteogenesis, making up for many shortcomings of existing spinal scaffolds. The scaffold composite material of the present invention is expected to promote the advancement of spinal implant technology and benefit more patients with spinal diseases. Bionic design can also be further introduced to achieve better matching of scaffold performance, morphology and the human spine.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a scaffold composite material, characterized in that: The following steps are involved: After mixing the graphene oxide dispersion and the polylactic acid dispersion, solidification and melt extrusion are performed in sequence to obtain a 3D printed graphene oxide / polylactic acid composite wire; 3D printing the 3D printed graphene oxide / polylactic acid composite wire in sequence to obtain a stent; The support is subjected to annealing treatment to obtain the support composite material.

2. The preparation method according to claim 1, characterized in that The solvent in the graphene oxide dispersion and the solvent in the polylactic acid dispersion independently include one or more of difluoromethane, fluorinated benzene, dimethylacetamide and dimethylformamide.

3. The preparation method according to claim 1, characterized in that: The mixing is carried out under stirring conditions, the stirring temperature is 28 to 35° C., and the time is 40 to 80 minutes; The polylactic acid dispersion is obtained by mixing polylactic acid and an organic solvent; the mixing temperature of the polylactic acid and the organic solvent is 28-35° C. and the mixing time is 90-180 min.

4. The preparation method according to claim 1, characterized in that: The curing method is vacuum drying; The vacuum drying is carried out at a temperature of 50-70° C. and for 24 hours.

5. The preparation method according to claim 1, characterized in that: The die temperature of the melt extrusion is 190-210° C., and the screw speed is 12-17 r / min.

6. The preparation method according to claim 1, characterized in that: The mass ratio of graphene oxide to polylactic acid in the 3D printed graphene oxide / polylactic acid composite wire is (0.001-0.0025):

1.

7. The preparation method according to claim 1, characterized in that: The annealing treatment is carried out in an oven; The temperature of the oven is 100-140° C., and the time is 30-90 minutes.

8. The scaffold composite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the scaffold composite material according to claim 8 in the preparation of medical implant materials.

10. The use according to claim 9, characterized in that The medical implant material is a spinal stent material.

Citation Information

Patent Citations

  • PLA / PTW wire material for 3D printing and preparation method thereof

    CN108299812A

  • Nano-silver / graphene oxide / degradable polymer composite bone scaffold material, antibacterial bone scaffold and preparation thereof

    CN110694116A

  • Guided tissue regeneration membrane and preparation method thereof

    CN112757743A

  • Heat-resistant biodegradable straw material and production process thereof

    CN114921075A

  • 3D printing reduced graphene oxide / polylactic acid composite wave-absorbing wire and preparation method thereof

    CN116575140A